2014
DOI: 10.1038/srep05357
|View full text |Cite
|
Sign up to set email alerts
|

Developing Gradient Metal Alloys through Radial Deposition Additive Manufacturing

Abstract: Interest in additive manufacturing (AM) has dramatically expanded in the last several years, owing to the paradigm shift that the process provides over conventional manufacturing. Although the vast majority of recent work in AM has focused on three-dimensional printing in polymers, AM techniques for fabricating metal alloys have been available for more than a decade. Here, laser deposition (LD) is used to fabricate multifunctional metal alloys that have a strategically graded composition to alter their mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(94 citation statements)
references
References 26 publications
(25 reference statements)
1
88
0
5
Order By: Relevance
“…At present, manufacturing such functionally tailored structures by the existing fusion-based AM processes is a challenge because of the differential thermal expansion coefficients of two alloys/materials that need to be fused. In cases, where this challenge is circumvented, avoiding undesirable intermetallic formation becomes a key issue (Hofmann et al, 2014). Since FBAM operates in solid state, the concern for thermal expansion is completely avoided while the intensified shearing during the process aids in controlling the size and distribution of intermetallics at the interface.…”
Section: Scope Of Friction-based Additive Technologiesmentioning
confidence: 99%
“…At present, manufacturing such functionally tailored structures by the existing fusion-based AM processes is a challenge because of the differential thermal expansion coefficients of two alloys/materials that need to be fused. In cases, where this challenge is circumvented, avoiding undesirable intermetallic formation becomes a key issue (Hofmann et al, 2014). Since FBAM operates in solid state, the concern for thermal expansion is completely avoided while the intensified shearing during the process aids in controlling the size and distribution of intermetallics at the interface.…”
Section: Scope Of Friction-based Additive Technologiesmentioning
confidence: 99%
“…For polymers, such systems have been demonstrated in inkjet 3D printing 23 ; for metals, such systems have been demonstrated in directed energy deposition, especially in laser engineered net shaping (LENS). [31][32][33][34] The right side shows a second type of mesoscale heterogeneous material systems, where each material voxel is assigned to be a specific constituent material. Such a material system can be fabricated by multi-nozzle extrusion, 35,36 inkjet 3D printing, 37,38 or directed energy deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Such a material system can be fabricated by multi-nozzle extrusion, 35,36 inkjet 3D printing, 37,38 or directed energy deposition. [31][32][33][34] Since multi-material additive manufacturing provides a unique pathway to implementing an arbitrary mesoscale material distribution, Yu, Cross, and Schuh 39 proposed to use computational optimization schemes for mesostructure design. By investigating the resistance to contact loading and bending as examples, they showed that significant improvement in material efficiency, load bearing capacity, and weight saving can be achieved by properly distributing the mechanical properties across the component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the increased application potential, and inspired from accessible published research in the more established associated fields of joining (e.g. welding) of dissimilar metals and manufacturing of functional graded materials, forays have already been made into additive manufacturing of multi-metal components by a few research groups [4] [5] [6] [7] [8]. However, additively manufactured multi-metal components are currently limited to research samples, primarily due to challenges in understanding, characterizing and controlling the involved manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%